Implications of short-circuit events on power cycling of 1.2-kV/20-A SiC MOSFET power modules. (September 2019) - Du, H.; Ceccarelli, L.; Iannuzzo, F.; Reigosa, P.D.
Abstract: When the device works in the real-field application, short-circuit events could happen along the whole lifetime of the component. In order to investigate the degradation effects of short-circuit events on power cycling, a mixed accelerated aging test combined with a repetitive short-circuit test has been performed for the 1.2-kV/20-A SiC MOSFET power module. The short-circuit robustness and repetitive short-circuit performance are analysed on the fresh device at first in order to understand the different levels of degradation. Then, the power cycling test is performed for two matched devices with the selected test conditions; one of them undergoes a number of short-circuit events and the other one, without short-circuit stress, is used as the reference. The experimental results exhibit a major implication of short-circuit degradation on power cycling and it would accelerate the degradation process of SiC MOSFETs.